Layer-by-Layer Fabrication of High-Performance Broadband Anti-reflection Coatings Comprising Oppositely Charged Nanosheets and Nanoparticles - Wu, Xin; Xue, Jinjuan; Zhou, Yuming; Ma, Shuaishuai; He, Man (Journal of Engineering and Technological Sciences, 2015)
In this study, we fabricated broadband anti-reflection coatings using a method based on layer-by-layer self assembly of positively charged layer double hydroxide (LDH) nanosheets and negatively charged silica nanoparticles via electrostatic interaction. Scanning electron microscopy and atomic force microscopy were used to observe the morphology, structure, and surface topography of LDH/SiO2 multilayer coatings. The anti-reflection properties of the coatings were investigated by UV visible spectrophotometry. Glass substrates covered with the LDH/SiO2 multilayer coatings exhibited broadband anti-reflection properties. The obtained [LDH(0.4 g/L)/SiO2(25 nm)]8, [LDH(0.4 g/L)/SiO2(50 nm)]10, and [LDH(0.8 g/L)/SiO2(25 nm)]6 coatings exhibited the best broadband anti-reflection properties among the as-prepared LDH/SiO2 multilayer coatings with different deposition cycles. Transmission levels of 97% were achieved in these optimal systems. Moreover, a maximum transmittance of 98% was achieved at a wavelength of 550 nm in the [LDH(0.4 g/L)/SiO2(25nm)]8 system and at 700 nm in the [LDH(0.8 g/L)/SiO2(25nm)]6 system. Different packing patterns of the two oppositely charged nanomaterials (dense packing of LDH nanosheets and loose stacking of silica nanoparticles) and the moderate textured surface of the coatings contributed to the enhanced light transmission and reduced wavelength dependence in the UV visible spectral range.